The Links between Finance and Inequality: Channels and Evidence - Claessens, Stijn; Perotti, Enrico (Washington, DC: World Bank, 2012)
Much attention has been given to whether market reforms reduce or increase inequality. Inequality often reflects unequal access to productive opportunities and recent evidence has highlighted the presence of onerous barriers to entry, especially in developing countries. This paper focuses on the relationships between inequality and finance. In principle, a better financial system can help overcome barriers, and thereby increase economic growth and reduce inequality. It analyzes these various channels from inequality to financial sector reform and provides (case) evidence on them. The question of, how, given initial wealth and power distributions, financial (and other) reforms could be designed to improve access and prevent perverse outcomes. It concludes that more gradual reform allowing the buildup of various types of oversight institutions is necessary for countries with high inequality.